Hospital and out‐of‐hospital mortality in 670 hypertensive emergencies and urgencies. Issue 11 (3rd September 2017) - Guiga, Haythem; Decroux, Clémentine; Michelet, Pierre; Loundou, Anderson; Cornand, Dimitri; Silhol, François; Vaisse, Bernard; Sarlon‐Bartoli, Gabrielle
Abstract: Long‐term mortality in patients with acute severe hypertension is unclear. The authors aimed to compare short‐term (hospital) and long‐term (12 months) mortality in these patients. A total of 670 adults presenting for acute severe hypertension between January 1, 2015, and December 31, 2015, were included. A total of 57.5% were hypertensive emergencies and 66.1% were hospitalized: 98% and 23.2% of those with hypertensive emergencies and urgencies, respectively ( P  = .001). Hospital mortality was 7.9% and was significantly higher for hypertensive emergencies (12.5% vs 1.8%, P  = .001). At 12 months, 106 patients died (29.4%), mainly from hypertensive emergencies (38.9% vs 8.9%, P  = .001). Median survival was 14 days for neurovascular emergencies and 50 days for cardiovascular emergencies. Patients with hypertensive emergencies or urgencies had bad long‐term prognosis. Short‐term mortality is mainly caused by neurovascular emergencies, but cardiovascular emergencies are severe, with high mortality at 12 months. These results justify better follow‐up and treatment for these patients.